2013
DOI: 10.1186/1556-276x-8-473
|View full text |Cite
|
Sign up to set email alerts
|

High-performance solid-state supercapacitors based on graphene-ZnO hybrid nanocomposites

Abstract: In this paper, we report a facile low-cost synthesis of the graphene-ZnO hybrid nanocomposites for solid-state supercapacitors. Structural analysis revealed a homogeneous distribution of ZnO nanorods that are inserted in graphene nanosheets, forming a sandwiched architecture. The material exhibited a high specific capacitance of 156 F g−1 at a scan rate of 5 mV.s−1. The fabricated solid-state supercapacitor device using these graphene-ZnO hybrid nanocomposites exhibits good supercapacitive performance and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
76
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(86 citation statements)
references
References 43 publications
9
76
0
1
Order By: Relevance
“…As the scan rate increases from 10-500 mV/s, area under curve increases and the specific capacitance value decreases. This is because at lower scan rates electrolyte ions are completely diffused into the material and hence all the active surface of material can be utilized for charge storage whereas at high scan rates, diffusion limits the movement of electrolyte ions due to the time constraints and only the outer active surface is used for charge storage [3,56]. At very low scan rates, scan rate independent behavior of specific capacitance 20 may be expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the scan rate increases from 10-500 mV/s, area under curve increases and the specific capacitance value decreases. This is because at lower scan rates electrolyte ions are completely diffused into the material and hence all the active surface of material can be utilized for charge storage whereas at high scan rates, diffusion limits the movement of electrolyte ions due to the time constraints and only the outer active surface is used for charge storage [3,56]. At very low scan rates, scan rate independent behavior of specific capacitance 20 may be expected.…”
Section: Resultsmentioning
confidence: 99%
“…FZ-1 composite exhibits the smallest R ct of 0.31 KΩ, indicating the optimal composition of CNTs and ZnO that lowers the inter-granular electronic resistance among active materials and the contact resistance between the electrode and the current collector [20,56]. FCNTs is very important to obtain good electrochemical performance.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4(b-f) shows the CV curves of MnO 2, GM1, GM2, GM3 and GM4 electrodes respectively over a potential range of -1 to 1 V which still exhibited a nearly rectangular shape signifying good capacitive performance. It was observed that an increase in scan rate lead to an increase in the CV area of the elctrode reflecting good storage rate ability as reported by previous reports [35,45]. The specific capacitance (C s ) can be calculated from the CV curves by equation 2 below [35]:…”
Section: Resultsmentioning
confidence: 60%
“…The average energy density (E) and power density (P) of the electrochemical capacitors were calculated to further determine their electrochemical performance using the following equations [45]:…”
Section: Resultsmentioning
confidence: 99%
“…Several methods have been carried out to produce graphene/ZnO and graphene/Mn 2 O 3 composites. Other researchers have also synthesized graphene/ZnO and graphene/Mn 2 O 3 , as they appear to be promising materials for pseudocapacitors due to their superior electrochemical performance, environmental friendliness, and lower production costs [5]. The present research is mainly focused on synthesizing Reduced Graphene Oxide (RGO) by using Hummer's method.…”
Section: Introductionmentioning
confidence: 99%